L’obra teatral de Llorenç Villalonga - Simbor Roig, Vicent (Caplletra. Revista Internacional de Filologia, 2015)
This book analyzes the whole of Llorenç Villalonga’s dramatic production - the relationship between the theatrical plays and the novels, and the classification and study of the dramatic production - following two basic lines: circuit theatre (halfway between comedy and customs and manners scenes, an approach to tragedy, drama and high comedy) and innovative, ground-breaking theatre (the absurdities).